Penerapan Teknik Pengendalian Food Cost Untuk Mengurangi Pemborosan Bahan Baku pada Pastry di Padma Resort Legian Kuta Bali - Ni Made Dwi Puspita Anggreni; I Made Bayu Wisnawa; Ni Nyoman Rusmiati (Ekodestinasi, 2026)
The hospitality industry requires effective cost control to maintain operational efficiency, particularly in the Food and Beverage department. The pastry section is highly vulnerable to waste due to its use of high-cost and perishable raw materials. This study aims to analyze the implementation of food cost control techniques to reduce raw material waste in the Pastry Department at Padma Resort Legian, Bali. This research uses a qualitative descriptive approach with field research methods. Data were collected through observation, interviews, and documentation involving pastry staff, supervisors, and cost control personnel. The results show that food cost control techniques have been applied through standard recipes, portion control, inventory management using forecasting and FIFO methods, variance analysis, and waste monitoring. However, several obstacles were identified, including human error, inconsistent implementation of SOPs, inadequate procurement specifications, and unstable storage conditions. To overcome these challenges, the department implemented corrective actions such as waste tracking systems, yield optimization, improved coordination, and regular staff briefings. Overall, the implementation is effective but requires stronger consistency and supervision to achieve optimal efficiency.